A platinum catalyst, its preparation method and application
The preparation of B/N doped graphene coated nanospheres by emulsion method and depositing Sn/Ni oxide-loaded platinum was solved, which solved the problems of weakening performance, high cost and easy poisoning of platinum catalysts during use, and achieved high catalytic activity and Durability, suitable for reactions such as ammonia oxidation, petroleum hydrocarbon reforming, etc.
Patent Information
- Application Number
- CN202410888260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-07-04
AI Technical Summary
During the use of existing platinum catalysts, there are problems such as the catalytic performance weakening in the later stage, high cost, easy poisoning, agglomeration and shedding, and the complex structure can easily lead to unstable performance.
Porous carbon nanospheres were prepared by emulsion method, spray-dried to form B/N doped wrinkled graphene coated nanospheres, and Sn/Ni oxide was deposited on their surface, and finally platinum was supported to form a platinum catalyst.
It improves the durability and catalytic activity of platinum catalysts, prevents the agglomeration and shedding of the catalysts, enhances the dispersion, and has broad application prospects.
Smart Images

Figure BDA0004926683000000111 
Figure BDA0004926683000000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a platinum catalyst and a preparation method and application thereof. Background Art
[0002] As is well known, platinum catalyst (also known as platinum catalyst) is a general term for catalysts made with platinum metal as the primary active component. These catalysts are made using platinum mesh, platinum black, or platinum supported on supports such as alumina. They may also contain promoters such as rhenium metal. They are primarily used in processes such as ammonia oxidation, petroleum hydrocarbon reforming, oxidation and hydrogenation of unsaturated compounds, and the removal of carbon monoxide and nitrogen oxides from gases. They are important industrial catalysts, characterized by high catalytic activity, strong selectivity, ease of preparation, and minimal usage. Their catalytic performance can be optimized through modifications and improvements to the manufacturing process, as well as through compounding with other metals or promoters. Existing platinum catalysts are typically added to the reactants in powder form, making filtration and separation difficult. Furthermore, active sites are often consumed in large quantities during the initial reaction, resulting in a weakening of the catalyst's performance later on, requiring recovery. Furthermore, these catalysts are costly and susceptible to poisoning, losing their catalytic activity, particularly in the presence of CO and H₂S. Therefore, the development of new platinum catalysts is imperative.
[0003] Chinese patent document CN207839011U relates to a slow-release platinum catalyst composite material, including a carrier core, a porous polymer layer coated on the outer surface of the carrier core, and a temperature-sensitive polymer layer coated on the outer surface of the porous polymer layer, wherein the porous polymer layer is a polypropylene porous membrane, and the carrier core is an alumina carrier loaded with a platinum catalyst. This ensures that the contact between the reactants and the catalyst is slow or gradual, ensuring the smooth progress of the reaction and suppressing the reaction from being too intense. However, the catalyst structure is complex, and delamination is prone to occur between the layers, resulting in poor performance stability of the platinum catalyst. Summary of the Invention
[0004] The purpose of the present invention is to provide a platinum catalyst and its preparation method and application, which has a high Pt loading and strong action force, is conducive to preventing catalyst agglomeration and shedding, improves the durability of the catalyst, and has high catalytic activity and good dispersibility, and has broad application prospects.
[0005] The technical solution of the present invention is achieved as follows:
[0006] The present invention provides a method for preparing a platinum catalyst. The method comprises the following steps: preparing porous carbon nanospheres by an emulsion method followed by carbonization; spray drying and reduction to prepare B / N-doped wrinkled graphene-coated nanospheres; depositing Sn / Ni oxides on the surface; and then loading platinum to prepare the platinum catalyst.
[0007] As a further improvement of the present invention, the following steps are included:
[0008] S1. Preparation of porous carbon nanospheres: A porogen, an emulsifier, and sodium alginate are dissolved in water, added dropwise to fish oil, emulsified, and a calcium chloride solution is added dropwise. The mixture is solidified, centrifuged, washed, dried, and carbonized to produce porous carbon nanospheres.
[0009] S2. Preparation of B / N-doped wrinkled GO-coated nanospheres: Boric acid and urea were added to a graphene oxide aqueous dispersion and stirred to mix uniformly. Porous carbon nanospheres were added and dispersed uniformly, and spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres.
[0010] S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced with hydrazine hydrate vapor to obtain B / N-doped wrinkled graphene-coated nanospheres;
[0011] S4. Sn / Ni oxide deposition: dissolving tin salt and nickel salt in water, adding B / N-doped wrinkled graphene-coated nanospheres, adding citric acid, stirring to react, drying, and calcining to obtain Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres;
[0012] S5. Preparation of platinum catalyst: Add Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres to anhydrous ethanol, add chloroplatinic acid ethanol solution, stir at room temperature, add polyvinyl pyrrolidone and sodium borohydride, stir to react, wash, and dry to obtain a platinum catalyst.
[0013] As a further improvement of the present invention, the mass ratio of the porogen, emulsifier and sodium alginate in step S1 is 1-2:0.5-1:25-30, the curing is room temperature curing for 20-40 minutes, and the carbonization temperature is 1200-1400° C. for 2-4 hours.
[0014] Preferably, the porogen is selected from at least one of cetyltrimethylammonium chloride, cetyltrimethylammonium bromide, cetyldimethylbenzylammonium chloride and cetyldimethylbenzylammonium bromide.
[0015] Preferably, the emulsifier is selected from at least one of Tween-20, Tween-40, Tween-60, Tween-80 and Tween-85.
[0016] As a further improvement of the present invention, the mass ratio of boric acid, urea, graphene oxide aqueous dispersion, and porous carbon nanospheres in step S2 is 1-2:0.9-1.2:100:20-25, and the concentration of the graphene oxide aqueous dispersion is 0.5-1 mg / mL.
[0017] As a further improvement of the present invention, the reduction time in step S3 is 10-12 hours.
[0018] As a further improvement of the present invention, the mass ratio of the tin salt, nickel salt, B / N-doped wrinkled graphene-coated nanospheres, and citric acid in step S4 is 3-5:2-4:15-20:5-7, the calcination temperature is 500-600° C., and the time is 1-3 h.
[0019] Preferably, the tin salt is selected from at least one of tin chloride and tin nitrate, and the nickel salt is selected from at least one of nickel chloride and nickel nitrate.
[0020] As a further improvement of the present invention, in step S5, the mass ratio of the Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres, chloroplatinic acid, polyvinyl pyrrolidone and sodium borohydride is 100:4-7:1-2:0.8-1.2, and the stirring reaction time is 3-5 hours.
[0021] As a further improvement of the present invention, the present invention specifically comprises the following steps:
[0022] S1. Preparation of porous carbon nanospheres: 1-2 parts by weight of a porogen, 0.5-1 parts by weight of an emulsifier, and 25-30 parts by weight of sodium alginate are dissolved in 200 parts by weight of water, added dropwise to 500 parts by weight of fish oil, emulsified, and 10-15 parts by weight of a 3-5 wt% calcium chloride solution is added dropwise. The mixture is cured at room temperature for 20-40 min, centrifuged, washed, dried, and carbonized at 1200-1400°C for 2-4 h to obtain porous carbon nanospheres.
[0023] S2. Preparation of B / N-doped wrinkled GO-coated nanospheres: 1-2 parts by weight of boric acid and 0.9-1.2 parts by weight of urea were added to 100 parts by weight of a 0.5-1 mg / mL aqueous dispersion of graphene oxide, and the mixture was stirred and mixed uniformly. 20-25 parts by weight of porous carbon nanospheres were added, dispersed uniformly, and spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres.
[0024] S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced with hydrazine hydrate vapor for 10-12 h to obtain B / N-doped wrinkled graphene-coated nanospheres;
[0025] S4. Sn / Ni oxide deposition: 3-5 parts by weight of tin salt and 2-4 parts by weight of nickel salt are dissolved in 200 parts by weight of water, 15-20 parts by weight of B / N-doped wrinkled graphene-coated nanospheres are added, and 5-7 parts by weight of citric acid are added. The mixture is stirred for 2-4 hours, dried, and calcined at 500-600°C for 1-3 hours to obtain Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres.
[0026] S5. Preparation of platinum catalyst: add 100 parts by weight of Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 4-7 parts by weight of chloroplatinic acid, stir at room temperature for 1-2 hours, add 1-2 parts by weight of polyvinyl pyrrolidone and 0.8-1.2 parts by weight of sodium borohydride, stir and react for 3-5 hours, wash, and dry to obtain a platinum catalyst.
[0027] The present invention further protects a platinum catalyst prepared by the above preparation method.
[0028] The present invention further protects the use of the above platinum catalyst in the catalytic reactions of ammonia oxidation, petroleum hydrocarbon reforming, unsaturated compound oxidation and hydrogenation, and removal of carbon monoxide and nitrogen oxides.
[0029] The present invention has the following beneficial effects:
[0030] Nanocarbon materials have advantages such as high conductivity and high specific surface area, but they also suffer from electrochemical corrosion and catalyst agglomeration. The present invention prepares porous sodium alginate nanospheres using an emulsion method. These are then carbonized at high temperatures to produce porous carbon nanospheres. The surface of the nanospheres is coated with graphene oxide doped with boron and nitrogen. Spray drying is then used to give the surface graphene oxide a wrinkled morphology, further increasing the specific surface area of the material. These defect sites, formed through reduction, can directly serve as catalytic sites to enhance catalytic activity. These defect sites can also function as co-catalysts by altering the catalyst's electronic structure, affecting the kinetics and selectivity of the catalytic reaction. This not only facilitates the uniform dispersion of the Pt metal catalyst on the carrier and prevents Pt agglomeration, but also increases its catalytic activity and durability.
[0031] Boron doping, due to the significant difference in electronegativity between boron and oxygen, easily adsorbs oxygen-containing groups, which helps reduce the adsorption of toxic oxygen-containing intermediates by Pt metal. Furthermore, since boron has a lower electronegativity than carbon, boron doping results in a localized positive charge in the carbon material, resulting in a higher spin density, which facilitates the adsorption of reactants and enhances catalytic activity. Nitrogen doping, on the other hand, helps strengthen the weak binding force between Pt and the support. Nitrogen atoms are similar in size to carbon atoms, facilitating their replacement by carbon atoms in the carbon material's lattice, thereby altering the electronic structure of the carbon material itself and strengthening the interaction between the Pt metal catalyst and the support. It can also form chemical bonds with carbon atoms, creating a large number of defect sites that facilitate catalyst loading. The doping of both has a synergistic effect, improving catalytic activity and durability.
[0032] The deposition of metal oxides forms a strong metal-support interaction with the carbon support, modifying the electronic structure of Pt, creating an electron-rich surface and promoting the desorption of poisoning intermediates, thereby enhancing the activity and durability of the catalyst. The interaction between SnO2 and NiO and the support forms a Pt-SnO2-NiO-C domain, which modifies the Pt metal electronic structure and adjusts the d-band center, exhibiting high activity. It also strengthens the adsorption between the Pt metal and the support, preventing catalyst agglomeration and shedding, and improving the catalyst's durability.
[0033] The platinum catalyst prepared by the present invention has a high Pt loading and a strong action force, which is beneficial to preventing the catalyst from agglomerating and falling off, thereby improving the durability of the catalyst. In addition, the catalyst has high catalytic activity and good dispersibility, and has broad application prospects. DETAILED DESCRIPTION
[0034] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0035] Graphene oxide aqueous dispersion was either prepared in the laboratory or purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.
[0036] Example 1
[0037] This embodiment provides a method for preparing a platinum catalyst, which specifically includes the following steps:
[0038] S1. Preparation of porous carbon nanospheres: 1 part by weight of the porogen hexadecyltrimethylammonium bromide, 0.5 parts by weight of Tween-60, and 25 parts by weight of sodium alginate were dissolved in 200 parts by weight of water and added dropwise to 500 parts by weight of fish oil. The mixture was emulsified at 10,000 rpm for 15 minutes, and 10 parts by weight of a 3 wt% calcium chloride solution was added dropwise. The mixture was cured at room temperature for 20 minutes, centrifuged, washed, dried, and carbonized at 1200°C for 2 hours to obtain porous carbon nanospheres.
[0039] Preparation of B / N-doped wrinkled GO-coated nanospheres: 1 part by weight of boric acid and 0.9 parts by weight of urea were added to 100 parts by weight of a 0.5 mg / mL aqueous dispersion of graphene oxide, stirred and mixed for 10 minutes, and 20 parts by weight of porous carbon nanospheres were added. Ultrasonic dispersion was performed at 1000 W for 15 minutes, and the mixture was spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres.
[0040] S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced with hydrazine hydrate vapor for 10 h to obtain B / N-doped wrinkled graphene-coated nanospheres;
[0041] S4. Sn / Ni oxide deposition: 3 parts by weight of tin chloride and 2 parts by weight of nickel chloride were dissolved in 200 parts by weight of water, 15 parts by weight of B / N-doped wrinkled graphene-coated nanospheres were added, and 5 parts by weight of citric acid were added. The mixture was stirred for 2 h, dried, and calcined at 500°C for 1 h to prepare Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres.
[0042] S5. Preparation of platinum catalyst: Add 100 parts by weight of Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 4 parts by weight of chloroplatinic acid, stir at room temperature for 1 hour, add 1 part by weight of polyvinyl pyrrolidone and 0.8 parts by weight of sodium borohydride, stir and react for 3 hours, wash, and dry to obtain a platinum catalyst.
[0043] Example 2
[0044] This embodiment provides a method for preparing a platinum catalyst, which specifically includes the following steps:
[0045] S1. Preparation of porous carbon nanospheres: 2 parts by weight of the porogen hexadecyltrimethylammonium bromide, 1 part by weight of Tween-80, and 30 parts by weight of sodium alginate were dissolved in 200 parts by weight of water and added dropwise to 500 parts by weight of fish oil. The mixture was emulsified at 10,000 rpm for 15 minutes, and 15 parts by weight of a 5 wt% calcium chloride solution was added dropwise. The mixture was cured at room temperature for 40 minutes, centrifuged, washed, dried, and carbonized at 1400°C for 4 hours to obtain porous carbon nanospheres.
[0046] Preparation of B / N-doped wrinkled GO-coated nanospheres: 2 parts by weight of boric acid and 1.2 parts by weight of urea were added to 100 parts by weight of a 1 mg / mL aqueous dispersion of graphene oxide, stirred and mixed for 10 minutes, and 25 parts by weight of porous carbon nanospheres were added. Ultrasonic dispersion was performed at 1000 W for 15 minutes, and the mixture was spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres.
[0047] S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced with hydrazine hydrate vapor for 12 h to obtain B / N-doped wrinkled graphene-coated nanospheres;
[0048] S4. Sn / Ni oxide deposition: 5 parts by weight of tin chloride and 4 parts by weight of nickel chloride were dissolved in 200 parts by weight of water, 20 parts by weight of B / N-doped wrinkled graphene-coated nanospheres were added, and 7 parts by weight of citric acid were added. The mixture was stirred for 4 hours, dried, and calcined at 600°C for 3 hours to obtain Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres.
[0049] S5. Preparation of platinum catalyst: Add 100 parts by weight of Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 7 parts by weight of chloroplatinic acid, stir at room temperature for 2 hours, add 2 parts by weight of polyvinyl pyrrolidone and 1.2 parts by weight of sodium borohydride, stir and react for 5 hours, wash, and dry to obtain a platinum catalyst.
[0050] Example 3
[0051] This embodiment provides a method for preparing a platinum catalyst, which specifically includes the following steps:
[0052] S1. Preparation of porous carbon nanospheres: 1.5 parts by weight of a porogen, hexadecyltrimethylammonium bromide, 0.7 parts by weight of Tween-85, and 27 parts by weight of sodium alginate were dissolved in 200 parts by weight of water and added dropwise to 500 parts by weight of fish oil. The mixture was emulsified at 10,000 rpm for 15 minutes, and 12 parts by weight of a 4 wt% calcium chloride solution was added dropwise. The mixture was cured at room temperature for 30 minutes, centrifuged, washed, dried, and carbonized at 1,300°C for 3 hours to obtain porous carbon nanospheres.
[0053] Preparation of B / N-doped wrinkled GO-coated nanospheres: 1.5 parts by weight of boric acid and 1 part by weight of urea were added to 100 parts by weight of a 1 mg / mL aqueous dispersion of graphene oxide, stirred and mixed for 10 minutes, and 22 parts by weight of porous carbon nanospheres were added. Ultrasonic dispersion was performed at 1000 W for 15 minutes, and the mixture was spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres.
[0054] S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced with hydrazine hydrate vapor for 11 h to obtain B / N-doped wrinkled graphene-coated nanospheres;
[0055] S4. Sn / Ni oxide deposition: 4 parts by weight of tin nitrate and 3 parts by weight of nickel nitrate were dissolved in 200 parts by weight of water, 17 parts by weight of B / N-doped wrinkled graphene-coated nanospheres were added, and 6 parts by weight of citric acid were added. The mixture was stirred for 3 h, dried, and calcined at 550°C for 2 h to prepare Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres.
[0056] S5. Preparation of platinum catalyst: Add 100 parts by weight of Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 5.5 parts by weight of chloroplatinic acid, stir at room temperature for 1.5 hours, add 1.5 parts by weight of polyvinyl pyrrolidone and 1 part by weight of sodium borohydride, stir and react for 4 hours, wash, and dry to obtain a platinum catalyst.
[0057] Comparative Example 1
[0058] Compared with Example 3, the difference is that the porogen hexadecyltrimethylammonium bromide is not added in step S1.
[0059] The details are as follows:
[0060] S1. Preparation of porous carbon nanospheres: 2.2 parts by weight of Tween-85 and 27 parts by weight of sodium alginate were dissolved in 200 parts by weight of water, added dropwise to 500 parts by weight of fish oil, emulsified at 10,000 r / min for 15 minutes, and 12 parts by weight of 4 wt% calcium chloride solution was added dropwise. The mixture was cured at room temperature for 30 minutes, centrifuged, washed, dried, and carbonized at 1,300°C for 3 hours to obtain porous carbon nanospheres.
[0061] Comparative Example 2
[0062] Compared with Example 3, the difference is that boric acid is not added in step S2.
[0063] The details are as follows:
[0064] S2. Preparation of N-doped wrinkled GO-coated nanospheres: 2.5 parts by weight of urea were added to 100 parts by weight of a 1 mg / mL graphene oxide aqueous dispersion, stirred and mixed for 10 minutes, 22 parts by weight of porous carbon nanospheres were added, ultrasonically dispersed at 1000 W for 15 minutes, and spray-dried to obtain N-doped wrinkled GO-coated nanospheres.
[0065] Comparative Example 3
[0066] Compared with Example 3, the difference is that urea is not added in step S2.
[0067] The details are as follows:
[0068] Preparation of B-doped wrinkled GO-coated nanospheres: 2.5 parts by weight of boric acid were added to 100 parts by weight of a 1 mg / mL aqueous dispersion of graphene oxide, stirred and mixed for 10 minutes, 22 parts by weight of porous carbon nanospheres were added, ultrasonically dispersed at 1000 W for 15 minutes, and spray-dried to obtain B-doped wrinkled GO-coated nanospheres.
[0069] Comparative Example 4
[0070] Compared with Example 3, the difference is that in step S2, room temperature drying is used instead of spray drying.
[0071] The details are as follows:
[0072] S2. Preparation of B / N-doped wrinkled GO-coated nanospheres: Add 1.5 parts by weight of boric acid and 1 part by weight of urea to 100 parts by weight of 1 mg / mL graphene oxide aqueous dispersion, stir and mix for 10 minutes, add 22 parts by weight of porous carbon nanospheres, ultrasonically disperse at 1000 W for 15 minutes, and dry at room temperature to obtain B / N-doped wrinkled GO-coated nanospheres.
[0073] Comparative Example 5
[0074] Compared with Example 3, the difference is that steps S2 and S3 are not performed.
[0075] The details are as follows:
[0076] S1. Preparation of porous carbon nanospheres: 1.5 parts by weight of a porogen, hexadecyltrimethylammonium bromide, 0.7 parts by weight of Tween-85, and 27 parts by weight of sodium alginate were dissolved in 200 parts by weight of water and added dropwise to 500 parts by weight of fish oil. The mixture was emulsified at 10,000 rpm for 15 minutes, and 12 parts by weight of a 4 wt% calcium chloride solution was added dropwise. The mixture was cured at room temperature for 30 minutes, centrifuged, washed, dried, and carbonized at 1,300°C for 3 hours to obtain porous carbon nanospheres.
[0077] S2. Sn / Ni oxide deposition: 4 parts by weight of tin nitrate and 3 parts by weight of nickel nitrate were dissolved in 200 parts by weight of water, 17 parts by weight of porous carbon nanospheres were added, and 6 parts by weight of citric acid were added. The mixture was stirred for 3 hours, dried, and calcined at 550°C for 2 hours to prepare Sn / Ni oxide deposition nanospheres.
[0078] S5. Preparation of platinum catalyst: Add 100 parts by weight of Sn / Ni oxide deposited nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 5.5 parts by weight of chloroplatinic acid, stir at room temperature for 1.5 hours, add 1.5 parts by weight of polyvinyl pyrrolidone and 1 part by weight of sodium borohydride, stir and react for 4 hours, wash, and dry to obtain a platinum catalyst.
[0079] Comparative Example 6
[0080] Compared with Example 3, the difference is that tin nitrate is not added in step S4.
[0081] The details are as follows:
[0082] S4. Ni oxide deposition: dissolve 7 parts by weight of nickel nitrate in 200 parts by weight of water, add 17 parts by weight of B / N-doped wrinkled graphene-coated nanospheres, add 6 parts by weight of citric acid, stir and react for 3 hours, dry, and calcine at 550°C for 2 hours to obtain Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres.
[0083] Comparative Example 7
[0084] Compared with Example 3, the difference is that nickel nitrate is not added in step S4.
[0085] The details are as follows:
[0086] S4. Sn oxide deposition: dissolve 7 parts by weight of tin nitrate in 200 parts by weight of water, add 17 parts by weight of B / N-doped wrinkled graphene-coated nanospheres, add 6 parts by weight of citric acid, stir and react for 3 hours, dry, and calcine at 550°C for 2 hours to obtain Sn oxide-deposited B / N-doped wrinkled graphene-coated nanospheres.
[0087] Comparative Example 8
[0088] Compared with embodiment 3, the difference is that step S4 is not performed.
[0089] The details are as follows:
[0090] S1. Preparation of porous carbon nanospheres: 1.5 parts by weight of a porogen, hexadecyltrimethylammonium bromide, 0.7 parts by weight of Tween-85, and 27 parts by weight of sodium alginate were dissolved in 200 parts by weight of water and added dropwise to 500 parts by weight of fish oil. The mixture was emulsified at 10,000 rpm for 15 minutes, and 12 parts by weight of a 4 wt% calcium chloride solution was added dropwise. The mixture was cured at room temperature for 30 minutes, centrifuged, washed, dried, and carbonized at 1,300°C for 3 hours to obtain porous carbon nanospheres.
[0091] Preparation of B / N-doped wrinkled GO-coated nanospheres: 1.5 parts by weight of boric acid and 1 part by weight of urea were added to 100 parts by weight of a 1 mg / mL aqueous dispersion of graphene oxide, stirred and mixed for 10 minutes, and 22 parts by weight of porous carbon nanospheres were added. Ultrasonic dispersion was performed at 1000 W for 15 minutes, and the mixture was spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres.
[0092] S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced with hydrazine hydrate vapor for 11 h to obtain B / N-doped wrinkled graphene-coated nanospheres;
[0093] S4. Preparation of platinum catalyst: Add 100 parts by weight of B / N-doped wrinkled graphene-coated nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 5.5 parts by weight of chloroplatinic acid, stir at room temperature for 1.5 hours, add 1.5 parts by weight of polyvinyl pyrrolidone and 1 part by weight of sodium borohydride, stir and react for 4 hours, wash, and dry to obtain a platinum catalyst.
[0094] Test Example 1
[0095] The specific surface area and pore structure of the platinum catalysts prepared in Examples 1-3 and Comparative Examples 1-8 were tested using an ASAP2400 static nitrogen adsorption instrument from Mircomeritics, Inc., USA. The results are shown in Table 1.
[0096] Table 1
[0097] Group <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore diameter (nm) Example 1 885 0.585 4.59 Example 2 889 0.584 4.55 Example 3 892 0.589 4.57 Comparative Example 1 759 0.492 10.82 Comparative Example 2 824 0.567 5.52 Comparative Example 3 830 0.571 5.49 Comparative Example 4 702 0.478 8.28 Comparative Example 5 694 0.439 9.29 Comparative Example 6 879 0.578 6.82 Comparative Example 7 872 0.575 6.72 Comparative Example 8 867 0.570 6.04
[0098] It can be seen from the above table that the platinum catalysts prepared in Examples 1-3 of the present invention have a high specific surface area and a rich pore structure.
[0099] Test Example 2
[0100] The reaction was conducted in an internal circulation isotropic reactor manufactured by Autoclave Engineers, Inc., USA. Under isotropic conditions, the circulation motor speed was 1000 rpm. 2 mL of the platinum catalyst prepared in Examples 1-3 and Comparative Examples 1-8 was loaded and reduced in an atmosphere of H₂ (150 mL / min), 1.2 MPa, and 480°C for 2 hours. The reaction was then continued at 480°C, 500°C, and 520°C for 1.5 hours each at a space velocity of 3.0 / h and a H₂:n-heptane ratio of 1000:1 (volume ratio). The reaction activity was measured. The results are shown in Table 2.
[0101] Table 2
[0102]
[0103]
[0104] As can be seen from the above table, the platinum catalysts prepared in Examples 1-3 of the present invention have good high-temperature aromatization performance, high selectivity, and high catalytic activity.
[0105] The platinum catalyst prepared in Example 3 was then separated, washed with ethanol and deionized water, dried, and subjected to catalytic cycling at 500° C. for nine cycles, and its reaction activity was measured. The results are shown in Table 3.
[0106] Table 3
[0107] Number of reactions n-heptane conversion rate (%) Aromatization products / cracking products First time 95.1 1.89 Repeat once 94.8 1.88 Repeat 2 times 94.5 1.88 Repeat 3 times 94.2 1.86 Repeat 4 times 93.6 1.84 Repeat 5 times 93.0 1.83 Repeat 6 times 92.1 1.81 Repeat 7 times 91.4 1.80 Repeat 8 times 90.7 1.78 Repeat 9 times 89.2 1.75
[0108] It can be seen from the above table that the platinum catalyst prepared in Example 3 of the present invention still has good catalytic activity after multiple catalysis.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a platinum catalyst, characterized in that: Porous carbon nanospheres were prepared by emulsion method followed by carbonization, and B / N-doped wrinkled graphene-coated nanospheres were prepared by spray drying and reduction, Sn / Ni oxides were deposited on the surface, and then platinum was loaded to prepare platinum catalysts; The following steps are involved: S1. Preparation of porous carbon nanospheres: dissolving a porogen, an emulsifier and sodium alginate in water, dropping into fish oil, emulsifying, dropping a calcium chloride solution, solidifying, centrifuging, washing, drying, and carbonizing to obtain porous carbon nanospheres; S2. Preparation of B / N-doped wrinkled GO-coated nanospheres: Adding boric acid and urea to a graphene oxide aqueous dispersion, stirring and mixing uniformly, adding porous carbon nanospheres, dispersing uniformly, and spray drying to obtain B / N-doped wrinkled GO-coated nanospheres; S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres are reduced by hydrazine hydrate vapor to obtain B / N-doped wrinkled graphene-coated nanospheres; S4. Sn / Ni oxide deposition: dissolving tin salt and nickel salt in water, adding B / N doped wrinkled graphene coated nanospheres, adding citric acid, stirring to react, drying, and calcining to obtain Sn / Ni oxide deposited B / N doped wrinkled graphene coated nanospheres; S5. Preparation of platinum catalyst: Add Sn / Ni oxide deposited B / N doped wrinkled graphene coated nanospheres into anhydrous ethanol, add chloroplatinic acid ethanol solution, stir at room temperature, add polyvinyl pyrrolidone and sodium borohydride, stir to react, wash, and dry to obtain a platinum catalyst.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the porogen, the emulsifier and the sodium alginate is 1-2:0.5-1:25-30, the curing is room temperature curing for 20-40 minutes, the carbonization temperature is 1200-1400° C., and the time is 2-4 hours.
3. The preparation method according to claim 1, characterized in that: The mass ratio of boric acid, urea, graphene oxide aqueous dispersion and porous carbon nanospheres in step S2 is 1-2:0.9-1.2:100:20-25, and the concentration of the graphene oxide aqueous dispersion is 0.5-1 mg / mL.
4. The preparation method according to claim 1, characterized in that: The reduction time in step S3 is 10-12 hours.
5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the tin salt, the nickel salt, the B / N-doped wrinkled graphene-coated nanospheres, and the citric acid is 3-5:2-4:15-20:5-7, the calcination temperature is 500-600° C., and the time is 1-3 h.
6. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of the Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres, chloroplatinic acid, polyvinyl pyrrolidone and sodium borohydride is 100:4-7:1-2:0.8-1.2, and the stirring reaction time is 3-5h.
7. The preparation method according to claim 1, characterized in that: The specific steps include: S1. Preparation of porous carbon nanospheres: 1-2 parts by weight of a porogen, 0.5-1 parts by weight of an emulsifier and 25-30 parts by weight of sodium alginate are dissolved in 200 parts by weight of water, added dropwise to 500 parts by weight of fish oil, emulsified, 10-15 parts by weight of a 3-5wt% calcium chloride solution is added dropwise, cured at room temperature for 20-40 min, centrifuged, washed, dried, and carbonized at 1200-1400° C. for 2-4 h to obtain porous carbon nanospheres; S2. Preparation of B / N-doped wrinkled GO-coated nanospheres: 1-2 parts by weight of boric acid and 0.9-1.2 parts by weight of urea are added to 100 parts by weight of a 0.5-1 mg / mL aqueous dispersion of graphene oxide, stirred and mixed uniformly, 20-25 parts by weight of porous carbon nanospheres are added, dispersed uniformly, and spray-dried to obtain B / N-doped wrinkled GO-coated nanospheres; S3. Reduction: The B / N-doped wrinkled GO-coated nanospheres were reduced by hydrazine hydrate vapor for 10-12 h to obtain B / N-doped wrinkled graphene-coated nanospheres; S4. Sn / Ni oxide deposition: 3-5 parts by weight of tin salt and 2-4 parts by weight of nickel salt are dissolved in 200 parts by weight of water, 15-20 parts by weight of B / N doped wrinkled graphene-coated nanospheres are added, 5-7 parts by weight of citric acid are added, stirred for reaction for 2-4 hours, dried, and calcined at 500-600° C. for 1-3 hours to obtain Sn / Ni oxide-deposited B / N doped wrinkled graphene-coated nanospheres; S5. Preparation of platinum catalyst: Add 100 parts by weight of Sn / Ni oxide-deposited B / N-doped wrinkled graphene-coated nanospheres to 500 parts by weight of anhydrous ethanol, add 50 parts by weight of an ethanol solution containing 4-7 parts by weight of chloroplatinic acid, stir at room temperature for 1-2 hours, add 1-2 parts by weight of polyvinyl pyrrolidone and 0.8-1.2 parts by weight of sodium borohydride, stir the reaction for 3-5 hours, wash, and dry to obtain a platinum catalyst.
8. A platinum catalyst prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the platinum catalyst as claimed in claim 8 in the catalytic reactions of ammonia oxidation, petroleum hydrocarbon reforming, unsaturated compound oxidation and hydrogenation, and removal of carbon monoxide and nitrogen oxides.
Citation Information
Patent Citations
Slowly -releasing type platinum catalyst combined material
CN207839011U
Fuel cell catalyst taking multi-element compound as carrier and preparation method thereof
CN101944620A
Preparation method and application of electrode active material of nitrogen-doped porous carbon
CN112447412A
